Multiple cutaneous ulcers revealing a primary cutaneous Epstein‐Barr virus‐positive diffuse large B‐cell lymphoma. Issue 12 (10th August 2020) - Tedbirt, Billal; Dubois, Sydney; Cellier, Lucie; Carvalho, Priscille; Stamatoullas, Aspasia; Courville, Philippe; Deschamps‐Huvier, Aurélie; Etancelin, Pascaline; Deniel, Anne; Tilly, Hervé; Jardin, Fabrice; Joly, Pascal; et al.
Abstract: Primary cutaneous EBV‐positive diffuse large B‐cell lymphoma is an exceptional and aggressive neoplasia with a poorer prognosis than other cutaneous lymphoma. Our observation points out the rarity of the presentation and the dismal clinical course. Abstract : Primary cutaneous EBV‐positive diffuse large B‐cell lymphoma is an exceptional and aggressive neoplasia with a poorer prognosis than other cutaneous lymphoma. Our observation points out the rarity of the presentation and the dismal clinical course.